The Role of Exercise in Preventing and Treating Depression - Schuch, Felipe Barreto; Stubbs, Brendon (Current sports medicine reports, 2019)
Depression is a leading cause of global burden. The mainstay of treatment is pharmacological and psychological interventions. While effective, not all people will respond to those treatments and alternative approaches for preventing and treating depression are required. Recent literature has demonstrated that higher physical activity (PA) levels and exercise confer protective effects on incident depression. Also, exercise has demonstrated efficacy on reducing symptoms for people with depression. Despite its effectiveness, similar to other treatments, some people may benefit more from exercise and identifying these potential predictors of response is necessary to deal with patients' and professionals' expectations. Dropout from exercise interventions is comparable to dropout from other treatments for depression and similar to dropout from exercise in other clinical populations. However, some strategies to increase adherence are important. In the present article, we provide an updated overview of the use of PA and exercise for the prevention and treatment of depression.